Gharar Konsep Memahami dalam Fiqih: Definisi dan Implikasinya dalam Transaksi - Muthia Azzahra; Lara Dwi Alma; Intan Nuraini Azzahra; Wismanto Wismanto (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
The concept of gharar in Islamic jurisprudence refers to uncertainty and speculation in transactions, which is prohibited due to its potential to cause loss and injustice. This study aims to examine the definitions, forms, and implications of gharar in modern economic transactions. Using a qualitative method with a literature review approach, data were collected from fiqh texts, books, and scholarly articlesThe findings indicate that gharar can be categorized into minor gharar, which may be tolerated, and major gharar, which is prohibited. Transactions such as conventional insurance and futures trading often involve gharar, but contemporary scholars provide boundaries to distinguish permissible uncertainty from prohibited uncertainty. Therefore, principles of openness, transparency, and clear agreements should be applied to avoid gharar in transactions.